Anak Berkebutuhan Khusus dalam Perspektif Psikologi Pendidikan Islam - Sangadah, Siti; Sayidah, Aminatus; Rokhimah, Siti (Lembaga Yasin AlSys, 2025)
Children with special needs are individuals who differ from typical children in physical, intellectual, emotional, social, or behavioral aspects. From the perspective of Islamic educational psychology, their existence is viewed as part of Allah SWT’s divine will, to be accepted with compassion and responsibility. This study aims to examine the role of Islamic educational psychology in understanding, supporting, and developing the potential of children with special needs. The research adopts a library study method with a descriptive-qualitative approach. The findings reveal that Islamic educational psychology emphasizes spiritual values, the principle of rahmah (compassion), and an understanding of each child’s fitrah and unique potential. Islam promotes inclusivity and respect for every individual without discrimination, including in educational contexts. Therefore, the roles of educators and parents are crucial in creating a learning environment that is friendly, supportive, and empowering for children with special needs. In conclusion, Islamic educational psychology offers a strong foundation for educating children with special needs in an empathetic, patient, and dignified manner, recognizing their humanity as creations of Allah.